Inclusive policies and the permanence of students with disabilities in higher education 2024 - Terranova Barrezueta, Aida Elizabeth (2024)
The situations of disability of students in public and private universities in Ecuador and the use of inclusive policies represent a point of analysis and institutional application worthy of research. Through the implementation and evaluation of these policies, it is intended to guarantee equitable access to education, while promoting an inclusive academic environment. The research aimed to determine the relationship between inclusive policies and the permanence of students with disabilities at the University of Guayaquil during the fiscal period 2023, through a quantitative approach, non-experimental design, correlational scope, and crosssectional section. The adaptation of perception instruments on inclusive policies and student permanence was used, which were validated by experts in addition to establishing adequate reliability indices, for a total sample of 113 students. Among its results, it evidenced a medium perception of inclusive policies with 56.64% by students, about their application in higher education institutions; in relation to the perception of student permanence, a mean perception of 62.83% by students corresponded. Likewise, a positive and significant relationship was denoted between both inclusive policies and the permanence of students with disabilities in the university. In conclusion, as the application of inclusive policies is perceived, the permanence of students with disabilities is guaranteed.